(untitled) (American International Journal of Economics and Finance Research, 2020)
This empirical study estimates and considers the impact of military expenditure on economic growth of Afghanistan for the period of 2004-2018 by applying the VAR model and VAR Granger causality (1980). The model is run by having the dependent (predicted) variable of economic growth and independent variable of military spending and employment. Ultimately, this analysis revealed that arm expenses do not have a significant effect on the economic growth of Afghanistan for the 15 years period from 2004-2018. And after running the VAR Granger causality it revealed that if some policy changes accrue to the GDP or economic then it will cause the military expenditure (unidirectional causality) and policy changes to the military expenditure will not cause GDP. According to the joint test, it is seen that if some policy changes accrue to the employment and military expenditure so it will cause GDP, if some policy changes accrue to the employment and GDP so it will cause military expenditure.